Production Strategy Selection Based on Diagnostics of the Economic Potential of an Industrial Enterprise - TINYAKOVA, VIKTORIYA I.; SUN, XINGYUAN; KONOVALOVA, OKSANA V.; KULYASOVA, ELENA V.; TARASOVA, VALENTINA N. (The journal of contemporary issues in business and government, 2021)
The article presents indicators for assessing the marketing and innovation, technical and technological, organizational, personnel and investment and sales potentials of an industrial enterprise, developed by the authors based on generalizing existing approaches to the interpretation of elements of economic potential and taking into account the challenges of neo- industrialization. A technique for measuring economic potential, which is based on the aggregation of expert assessments, is proposed. A mechanism has been developed for determining the production strategy of an enterprise and choosing directions for prospective investment based on estimates of the components of economic potential. The results presented in the article (method and mechanism) were tested at mechanical engineering enterprises. Their practical use allows comparing the strategic positions of enterprises and choosing the optimal vector of their development. The scientific and methodological provisions developed in the article can be used by industrial enterprises of various sectors of the economy in production management and researchers of production management problems for the development of the theory and practice of strategic planning and analysis of the resource potential of enterprises.